The Ross Sea and Amundsen Sea Ice–Sea Model (RAISE v1.0): a high-resolution ocean–sea ice–ice shelf coupling model for simulating the Dense Shelf Water and Antarctic Bottom Water in the Ross Sea, Antarctica - Z. Zhang; Z. Zhang; Z. Zhang; Z. Zhang; C. Xie; C. Wang; Y. Chen; H. Hu; X. Wang; X. Wang (Geoscientific Model Development)
The Ross Sea in the Southern Ocean is a key region for the formation of the Antarctic Bottom Water (AABW) that supplies the lower limb of the global overturning circulation and contributes to 20 %–40 % of the total AABW production. AABW primarily originates from polynyas characterized by strong sea ice production and ocean convection that lead to the formation of Dense Shelf Water (DSW), the precursor of AABW. The production and characteristics of DSW in the Ross Sea and AABW in the surrounding ocean are significantly affected by ice shelf meltwater transported from the nearby Amundsen Sea. The scarcity of long-term observations in the Ross Sea hinders the understanding of DSW and AABW variability, and numerical models are needed to explore the multi-scale variations in these water masses and the forcing mechanisms. In this work, a coupled high-resolution ocean–sea ice–ice shelf model is developed for the Ross Sea and Amundsen Sea, named the Ross Sea and Amundsen Sea Ice–Sea Model (RAISE). Detailed descriptions of the model configurations are provided. This study represents an attempt to thoroughly evaluate the DSW properties and associated ocean–sea ice–ice shelf coupling processes among modeling studies in the Southern Ocean, using multiple datasets including satellite-based observations and hydrographic measurements from the World Ocean Database, Argo profilers and seal-tag sensors. In particular, the modeled temporal variations in DSW properties in polynyas and key export passages are compared with long-term mooring observations, which are rarely seen in studies of the DSW temporal variability before. RAISE demonstrates a high skill level in simulating the observed sea ice production rates in the Ross Sea polynyas, and the modeled spatial and temporal variability in DSW are significantly and strongly correlated with observations. RAISE can also effectively capture the observed long-term freshening trend of DSW prior to 2014 and the rebounding of DSW salinity after 2014. RAISE shows an overestimate of DSW density in the Ross Sea, which is associated with an underestimate of ice shelf melting rates in the Amundsen Sea, missing ice shelf calving processes and subglacial discharge in the model. A sensitivity experiment simulating increased freshwater discharge from these processes can significantly improve the simulation of DSW properties.